2009
DOI: 10.1016/j.jde.2009.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Stability of boundary layer and rarefaction wave to an outflow problem for compressible Navier–Stokes equations under large perturbation

Abstract: In this paper, we investigate the large-time behavior of solutions to an outflow problem for compressible Navier-Stokes equations. In 2003, Kawashima, Nishibata and Zhu [S. Kawashima, S. Nishibata, P. Zhu, Asymptotic stability of the stationary solution to the compressible Navier-Stokes equations in the half space, Comm. Math. Phys. 240 (2003) 483-500] showed there exists a boundary layer (i.e., stationary solution) to the outflow problem and the boundary layer is nonlinearly stable under small initial perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…• For the outflow problem, Kawashima, Nishibata, and Zhu [4] and Kawashima and Zhu [5] showed that the boundary layer solution together with the superposition of the boundary layer solution and the rarefaction wave are asymptotically nonlinear stable under small initial perturbation, while Nakamura, Nishibata and Yuge [11] investigated the convergence rate toward the boundary layer solution. Recently, Huang and Qin [2] show that not only the boundary layer solution but also the superposition of the boundary layer solution and the rarefaction wave are still stable under large initial perturbation and improve the works of [4] and [5];…”
Section: Introductionmentioning
confidence: 99%
“…• For the outflow problem, Kawashima, Nishibata, and Zhu [4] and Kawashima and Zhu [5] showed that the boundary layer solution together with the superposition of the boundary layer solution and the rarefaction wave are asymptotically nonlinear stable under small initial perturbation, while Nakamura, Nishibata and Yuge [11] investigated the convergence rate toward the boundary layer solution. Recently, Huang and Qin [2] show that not only the boundary layer solution but also the superposition of the boundary layer solution and the rarefaction wave are still stable under large initial perturbation and improve the works of [4] and [5];…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this manuscript, we will concerned with the inflow problem (1.1). For the corresponding impermeable wall problem and outflow problem, those interested are referred to [13,16] and [4,6,8,9,10,19,20,27] and the references cited therein, respectively.…”
Section: The Inflow Problemmentioning
confidence: 99%
“…Since 1960s, people have discovered several methods to study the well-posedness of Milne problem, and apply them to asymptotic expansion. We refer to the references [15], [3], [4], [29], [20], [25], [13], [12], [1], [8], [11], [16], [19], [26], [5], [2], [10], [21], [22], [23], and [24] for more details. In 1979, diffusive limit of steady neutron transport equation was systematically investigated in [9] (see also [6] and [7]).…”
Section: )mentioning
confidence: 99%